2010
DOI: 10.1111/j.1540-8191.2010.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Coronary Artery-Right Ventricular Fistula with Multiple Ventricular Septal Defects

Abstract: The combination of posttraumatic coronary artery-right ventricular fistula and multiple ventricular septal defects is a rare and interesting phenomenon. We describe a case of a 19-year-old male with these findings following a blunt chest trauma after a motorcycle accident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This may occur as a result of direct cardiac impact or when the heart is compressed between the sternum and the spine. [3578111520] It has also been suggested that a healed congenital VSD with a weakened ventricular septum may re-open with significant blunt trauma to the chest. [6] Delayed inflammatory rupture is thought to occur when cardiac injury causes localised edema with disruption of microvascular flow, leading to infarction, septal liquefaction, and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur as a result of direct cardiac impact or when the heart is compressed between the sternum and the spine. [3578111520] It has also been suggested that a healed congenital VSD with a weakened ventricular septum may re-open with significant blunt trauma to the chest. [6] Delayed inflammatory rupture is thought to occur when cardiac injury causes localised edema with disruption of microvascular flow, leading to infarction, septal liquefaction, and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery rupture or coronary artery fistula from blunt thoracic trauma is very rare, and few cases associated with a traumatic ventricular septal defect have been described [24]. This is, to the best of our knowledge, the first reported case of coronary artery fistula (RCA to RA) and occlusion with an inferior MI that occurred following blunt chest trauma worldwide.…”
Section: Discussionmentioning
confidence: 95%
“…Mechanical septal rupture may occur as a result of direct cardiac impact or when the heart is compressed between the sternum and the spine. [ 2 5 7 8 9 ] It has also been suggested that a healed congenital VSD with a weakened ventricular septum may be re-opened with significant blunt trauma to the chest. [ 6 ] Delayed inflammatory rupture is thought to occur when cardiac injury leads to localized edema, disruption of microvascular flow, leading to infarction, septal liquefaction, and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Presenting signs are often masked by concomitant injuries, and the severity, presentation, and course are variable. [ 1 2 3 4 5 6 7 8 9 10 ] The mainstay of diagnosing VSDs is the transthoracic echocardiogram. This case report describes a rare case of acquired posttraumatic VSD as a complication of nonpenetrating chest trauma that occurred during a motor vehicle collision.…”
Section: Introductionmentioning
confidence: 99%